The Arabidopsis synaptotagmin SYTA regulates the cell-to-cell movement of diverse plant viruses - Uchiyama, Asako; Shimada-Beltran, Harumi; Levy, Amit; Zheng, Judy Y.; Javia, Parth A.; Lazarowitz, Sondra G. (Frontiers in Plant Science, 2014)
Synaptotagmins are a large gene family in animals that have been extensively characterized due to their role as calcium sensors to regulate synaptic vesicle exocytosis and endocytosis in neurons, and dense core vesicle exocytosis for hormone secretion from neuroendocrine cells. Thought to be exclusive to animals, synaptotagmins have recently been characterized in Arabidopsis thaliana, in which they comprise a five gene family. Using infectivity and leaf-based functional assays, we have shown that Arabidopsis SYTA regulates endocytosis and marks an endosomal vesicle recycling pathway to regulate movement protein-mediated trafficking of the Begomovirus Cabbage leaf curl virus (CaLCuV) and the Tobamovirus Tobacco mosaic virus (TMV) through plasmodesmata (Lewis and Lazarowitz, 2010). To determine whether SYTA has a central role in regulating the cell-to-cell trafficking of a wider range of diverse plant viruses, we extended our studies here to examine the role of SYTA in the cell-to-cell movement of additional plant viruses that employ different modes of movement, namely the Potyvirus Turnip mosaic virus (TuMV), the Caulimovirus Cauliflower mosaic virus (CaMV) and the Tobamovirus Turnip vein clearing virus (TVCV), which in contrast to TMV does efficiently infect Arabidopsis. We found that both TuMV and TVCV systemic infection, and the cell-to-cell trafficking of the their movement proteins, were delayed in the Arabidopsis Col-0 syta-1 knockdown mutant. In contrast, CaMV systemic infection was not inhibited in syta-1. Our studies show that SYTA is a key regulator of plant virus intercellular movement, being necessary for the ability of diverse cell-to-cell movement proteins encoded by Begomoviruses (CaLCuV MP), Tobamoviruses (TVCV and TMV 30K protein) and Potyviruses (TuMV P3N-PIPO) to alter PD and thereby mediate virus cell-to-cell spread.